Amplification-free CRISPR/Cas detection technology: challenges, strategies, and perspectives. (19th December 2022) - Li, Huimin; Xie, Yi; Chen, Fumin; Bai, Huiwen; Xiu, Leshan; Zhou, Xiaonong; Guo, Xiaokui; Hu, Qinqin; Yin, Kun
Abstract : This review summarizes the recent advances and the main strategies to improve the sensitivity of amplification-free CRISPR/Cas-based detection techniques. Abstract : Rapid and accurate molecular diagnosis is a prerequisite for precision medicine, food safety, and environmental monitoring. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas)-based detection, as a cutting-edged technique, has become an immensely effective tool for molecular diagnosis because of its outstanding advantages including attomolar level sensitivity, sequence-targeted single-base specificity, and rapid turnover time. However, the CRISPR/Cas-based detection methods typically require a pre-amplification step to elevate the concentration of the analyte, which may produce non-specific amplicons, prolong the detection time, and raise the risk of carryover contamination. Hence, various strategies for target amplification-free CRISPR/Cas-based detection have been developed, aiming to minimize the sensitivity loss due to lack of pre-amplification, enable detection for non-nucleic acid targets, and facilitate integration in portable devices. In this review, the current status and challenges of target amplification-free CRISPR/Cas-based detection are first summarized, followed by highlighting the four main strategies to promote the performance of target amplification-free CRISPR/Cas-based technology. Furthermore, we discuss future perspectives that will contribute to developing more efficient amplification-free CRISPR/Cas detection systems.